Medical case reports in the age of genomic medicine. Issue 10 (16th October 2015) - Cook, Matthew C
Abstract : The case report has been a pillar of medical literature but has been displaced recently because of inherent risks of bias. As we move towards precision medicine, however, the case report format could provide an important method for describing disease mechanisms based on rare genetic variants. Empirical evidence reveals that many previously unexplained Mendelian diseases are accounted for by rare heterozygous alleles, de novo mutations or compound heterozygous mutations, and that disease‐associated variants are often confined to the kindred of the affected individual. Elucidation of the phenotypes of these rare genetic variants will necessarily offer unique insights into disease mechanisms. Even when the association between variants in a specific gene and a disease has already been identified, individual cases are valuable. Allelic series extend both the clinical and laboratory phenotypes. Finally, the prevalence of a disease is not a reliable indicator of the therapeutic importance of the underlying mechanism, so resolving extreme phenotypes even in single cases has the potential to identify new treatment strategies relevant to more common disease.